Residential responses to cyclones: New evidence from Australia - Ha Trong Nguyen; Francis Mitrou (Global Labor Organization (GLO), 2024)
By leveraging randomly timed exposure to local cyclones as natural experiments, this study pioneers a comprehensive causal analysis of cyclone impacts on residential outcomes among Australian individuals. Drawing upon over two decades of nationally representative longitudinal data from the Household, Income and Labour Dynamics in Australia survey, coupled with historical cyclone records, individual fixed effects models uncover substantial increases in reported home damage. Planned relocation intentions and actual migration experiences show moderate increases, particularly in cases of higher cyclone severity and proximity. Additionally, these cyclones prompt individuals to acknowledge the significance of home-related insurance and actively seek coverage. Alongside long-distance domestic migration, insurance acquisition emerges as another alternative coping mechanism, effectively mitigating future repair costs. Extensive heterogeneity analyses reveal that the choice among these coping strategies depends on factors such as cyclone severity, age, prior homeownership, income, insurance coverage, rural/urban residence, coastal proximity, and community cyclone history. Moreover, the study identifies home damage from cyclones as a key factor driving observed migration patterns.
Keywords: G22; G52; J61; Q54; R23; 330; Natural Disasters; Migration; Insurance; Australia